Lack of Foreign Investments in the Non-Oil Sector of Azerbaijan - Yusifova, Aytaj; Mammadli, Rana; Mustafazada, Sona (ADA University, 2025)
This capstone project investigates the persistent underperformance of foreign direct investment (FDI) in Azerbaijan’s non-oil sectors despite government initiatives to diversify the economy. It focused on three main factors – economic reliance on oil revenues, restrictive legal and regulatory environment for foreign companies, and lack of high-skill labor force in non-oil sectors – which were found to hinder investment. Through qualitative analysis of policy documents, legal frameworks, and international economic reports, the study evaluates the impact of these constraints on Azerbaijan's investment climate. Three policy options – strategic financial incentives, legal and institutional reforms, and human capital development – were assessed based on 𝑒3𝑓2 framework made up of 5 critical indicators of policy success such as effectiveness, efficiency, equity, flexibility and feasibility. The research concludes that while Azerbaijan has made progress in promoting diversification, further legal and institutional reforms will strengthen investor trust, reduce governance-related risks which play essential role in attracting sustainable FDI into non-oil industries and fostering a more inclusive and diversified economic growth.
Keywords: Investments, Foreign -- Government policy -- Azerbaijan; Petroleum industry and trade -- Economic aspects -- Azerbaijan; Industrial policy -- Azerbaijan; Labor supply -- Skilled labor -- Azerbaijan; Human capital -- Economic development; Public and International Affairs